Costos unitarios y rentabilidad en la explotación del método de circado tajo 940-1 de la Empresa S.M.R.L. Minera Sayapullo, 2022 - Espejo Tamayo, Antobely Mercedes (2023)
The main objective of the research was to apply the exploitation of the circado method to reduce the mining cost and increase the profitability of the company S.M.R.L. Minera Sayapullo, 2022. The methodology used in the research was a non-experimental, descriptive, applicative design. The population consisted of all the pits of the El Cobre mine of S.M.R.L. Minera Sayapullo and the population consisted of Pit 940-1 of the San Lorenzo vein of S.M.R.L. For data collection, documentary analysis was used and to validate the hypothesis, the quality control of data where the probability is less than 5% with a critical value of 7.71 and an F statistic of 16177.19. The results obtained were that the exploitation of the circado method was applied to reduce dilution in the San Lorenzo vein, pit 940-1, where the total broken material with the circado method was 9.14 tons with a total of 150 explosives consumed and 30 drills drilled, giving an average of 4 ore. The unit costs of S.M.R.L. Minera Sayapullo in November, December and January 2022 were 58418.33 US$ for November, 58181.24 US$ for December and 58353.49 US$ for January. It was also possible to determine the profitability of S.M.R.L. in November, December and January 2022, which for November was 38731.17 US$, for December it was 38250.76 US$ and for January it was 38539.01 US$. Likewise, the break-even point calculated was 96 tons per month. Finally, it is concluded that November 2022 was the most profitable month for Minera Sayapullo S.M.R.L. when applying the mining by the Circado method.